Strategies for Implementing Personalized Learning in Rural Schools (The Education digest, 2017)
[...]many teachers in rural areas take on multiple subjects and grades, resulting in a lower likelihood that teachers have certification in all of their subjects. While there are unique considerations for each gear, two strategies are critically important across all gears: * District leaders must de- velop and communicate a clear vision and plan of action for transitioning to a personalized learning model. Because rural schools often serve as the heart of their communities, changes to long-standing norms and traditions and trade-offs tied to investments in innovation and change must be vetted and embraced by the community. [...]the leap to systematically collecting data on student learning and customizing instruction may not be as big as it may first seem. Rural schools tend to pay about two and a half times more for bandwidth than urban schools. [...]many rural school facilities need significant infrastructure upgrades to handle new technology.